Individual differences in theta-band oscillations in a spatial memory network revealed by electroencephalography predict rapid place learning. (April 2021) - Bauer, Markus; Buckley, Matthew G.; Bast, Tobias
Spatial memory has been closely related to the medial temporal lobe and theta oscillations are thought to play a key role. However, it remains difficult to investigate medial temporal lobe activation related to spatial memory with non-invasive electrophysiological methods in humans. Here, we combined the virtual delayed-matching-to-place task, reverse-translated from the watermaze delayed-matching-to-place task in rats, with high-density electroencephalography recordings. Healthy young volunteers performed this computerised task in a virtual circular arena, which contained a hidden target whose location moved to a new place every four trials, allowing the assessment of rapid memory formation. Using behavioural measures as predictor variables for source reconstructed frequency-specific electroencephalography power, we found that inter-individual differences in 'search preference' during 'probe trials', a measure of one-trial place learning known from rodent studies to be particularly hippocampus-dependent, correlated predominantly with distinct theta-band oscillations (approximately 7 Hz), particularly in the right temporal lobe, the right striatum and inferior occipital cortex or cerebellum. This pattern was found during both encoding and retrieval/expression, but not in control analyses and could not be explained by motor confounds. Alpha-activity in sensorimotor and parietal cortex contralateral to the hand used for navigation also correlated (inversely) with search preference. This latter finding likely reflects movement-related factors associated with task performance, as well as a frequency difference in (ongoing) alpha-rhythm for high-performers versus low-performers that may contribute to these results indirectly. Relating inter-individual differences in ongoing brain activity to behaviour in a continuous rapid place-learning task that is suitable for a variety of populations, we could demonstrate that memory-related theta-band activity in temporal lobe can be measured with electroencephalography recordings. This approach holds great potential for further studies investigating the interactions within this network during encoding and retrieval, as well as neuromodulatory impacts and age-related changes.